Are really digital natives so good? Relationship between digital skills and digital reading - Fajardo, Inmaculada; Villalta, Ester; Salmerón, Ladislao (Anales de Psicología / Annals of Psychology, 2015)
Digital reading literacy consists on the comprehension, use, reflection and enjoyment of written texts with the aim to fulfill our goals, to develop our knowledge and potential, and to participate in our society. Currently it is considered that “digital natives”, i.e. those students that have been raised surrounded by information technologies, poses the basic digital skills (such as using the mouse, the browser, …) required to develop digital reading skills. The present study tested this assumption, by means of a study in which students of 5th level of primary education and 3rd level of secondary education performed a series of digital reading tasks. In addition, students completed several objective tasks to measure their basic reading skills, and their printed reading comprehension. The results revealed that the groups assessed had difficulties in several basic digital skills, and that those skills are directly related to success rate in digital reading tasks. A regression analysis revealed that this relationship was independent of students’ printed reading skills, as well as of students’ navigation during the digital reading tasks. To conclude, we reflected on the need to consider the instruction of basic reading skills as part of the current efforts to improve digital reading literacy.